Analysis of Lasswell Communication Model in Marriage Services during the COVID-19 Pandemic at KUA - Dyna Mardiana; Mailin Mailin; Winda Kustiawan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The pandemic situation has hampered marriage services at the Office of Religious Affairs (KUA), one of which is in the South Binjai District, North Sumatra. The government's policy regarding the postponement of marriage in the midst of the COVID-19 outbreak in Indonesia resulted in the absence of registration and the marriage process for the bride and groom (catin) during the years 2020-2021. This condition is feared to increase the number of sexual crimes and adultery that violate state and religious laws. The purpose of this study was to analyze the Lasswell communication model carried out by KUA in South Binjai District in marriage services during the pandemic. The research method used is descriptive with a naturalistic approach. The theoretical reference is Lasswell's communication model. The data were collected through observation and in-depth interviews with a number of informants including the Head of KUA, South Binjai District, penghulu, Islamic religious educators (PNS and non-PNS), and general administrative staff, SIMKAH operators, and two informants from the catin party. This study concludes that the KUA of South Binjai District has implemented the Lasswell communication model, namely communicator, message, media ( channel ), communicant, and effects. However, its implementation has not been fully maximized because there are still obstacles to the use of the nationally integrated web-based SIMKAH application as an information channel. For this reason, KUA needs to combine conventional communication through face-to-face counseling, the installation of banners and posters, with the use of social media such as Facebook, Instagram, and YouTube.